Modelling for integrated drainage basin management - Abdul Hadi Harman Shah; Abdul Samad Hadi (Environmental Management Society, Malaysia, 2000)
Real world environmental processes are typically three dimensional, times dependent and complex. The processes also compose of non-linear behaviour, stochastic components and feedback loops over multiple time and space scales. To understand these in entirely are impossible and environmental managers and scientists often resort to the process of modelling in order to simplify real world processes. An integrated drainage basin management endeavour often requires the use of modelling to clarify the interpenetration of the different components, making sense of an otherwise extremely complex ecosystem. However, an understanding of what a model is capable of is important in order to use it as an enabling tool in environmental management. This paper presents a discussion on modelling a drainage basin for the purpose of development planning and environmental management. Using the Langat basin study as a case study, the paper outlines the objectives, interrelations and procedures in developing an environmental management model using the concepts of vulnerability and ecosystem health. The paper also discusses planning and management issues resulting from the development and use of the model. While the model itself is still a work in progress, the paper hopes to highlight significant considerations of using environment modelling for the purpose of integrated drainage basin management